Conflicting memories: the case of Coventry - Molina Iniesta, Mariano (Estoa. Journal of the Faculty of Architecture and Urbanism, 2017)
The article attempts to explain the project to rebuild Coventry Cathedral after World War II in the light of the processes of formation of collective memory studied by Sociology, highlighting the conflicting interests of a local community willing to overcome a painful past and a nation interested in using such past to develop a narrative of victimization and resurrection across the country. Moreover it presents the project in Coventry as an example of admonitory monument or Mahnmal, popularized at that time due to the inability to sustain a narrative of war in terms of courage and honor. Keywords: collective memory, Coventry, second postwar period, admonitory monument.